Sociodemographic pattern of drug abuser in the port city, Chittagong - Hasan, Md Shafiul; Islam, Md Azizul; Islam, Md Monirul (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i2.3822 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):4-6